ALLELOPATHIC EFFECTS OF SORGHUM AND SUNFLOWER WATER EXTRACTS ON GERMINATION AND SEEDLING GROWTH OF RICE (ORYZA SATIVA L.) AND THREE WEED SPECIES - K. Mubeen; M. A. Nadeem; A. Tanveer; Z. A. Zahir (Journal of Animal and Plant Sciences, 2012)
Laboratory experiments were conducted to evaluate the allelopathic effects of water extracts of sorghum and sunflower alone and in combination on the germination and seedling growth of rice and weeds viz: Trianthema portulacastrum, Dactyloctenium aegyptium and Eleusine indica. Distilled water treatment was included as control. In first experiment, the germinated seeds of rice and weeds were counted every day and removed from petri dishes. Whereas in second experiment, rice and weed seeds were sown in sand culture to assess their seedling growth. Experiments were laid out in completely randomized design under factorial arrangement. Sorghum and sunflower water extracts when applied in combination caused maximum inhibitory effects on time taken to 50 % germination, mean germination time of E. indica seeds and germination index of T. portulacastrum seeds as compared to the sole application of these water extracts. Water extracts of sorghum, sunflower when applied alone and in combination increased the root, shoot length and the seedling biomass of rice over control. Combined application of sorghum and sunflower water extracts caused maximum reduction in root length of T. portulacastrum. It can be concluded that combined application of sorghum and sunflower water extracts has overall more inhibitory effects on the germination of rice, T. portulacastrum, D. aegyptium and E. indica when compared to their sole application.
Keywords: Allelopathy; Dactyloctenium aegyptium; Eleusine indica; germination; Oryza sativa; seedling growth